2021
DOI: 10.1055/s-0040-1722626
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work after Primary Total Knee Arthroplasty under the Age of 65 Years: A Systematic Review

Abstract: A growing number of patients undergoing total knee arthroplasty (TKA) is at working age and need to return to work (RTW) after surgery. The aim of this systematic review is to give an overview of the literature regarding RTW after TKA and beneficial and limiting factors influencing this process. A systematic search in four electronic databases was conducted in November 2019 to identify studies describing RTW after primary TKA in patients aged 65 years or younger. Study characteristics and data on work status b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 22 publications
(48 reference statements)
8
34
0
Order By: Relevance
“…To ensure good external validity, we also advise this study to be a multicenter study to overcome bias introduced by the clinical involvent of the primary researcher. In comparison to other studies among working age patients with KA, the present patient characteristics were similar in terms of age, gender and educational level [6,15]. An important prognostic factor for RTW for patients with KA, are the physical job demands [15].…”
Section: Generalizabilitysupporting
confidence: 58%
See 2 more Smart Citations
“…To ensure good external validity, we also advise this study to be a multicenter study to overcome bias introduced by the clinical involvent of the primary researcher. In comparison to other studies among working age patients with KA, the present patient characteristics were similar in terms of age, gender and educational level [6,15]. An important prognostic factor for RTW for patients with KA, are the physical job demands [15].…”
Section: Generalizabilitysupporting
confidence: 58%
“…Physical therapy provided by primary care physical therapy outside the hospital is also in line with the right care in the right place, a main topic on the agenda of the Dutch National Health Care Institute (https://english.zorginstituutnederland.nl/). To increase the dose delivered, we advise to train the orthopedic surgeons to inform patients better about return to work after surgery and relevant prognostic factors, in line with recent studies[8, 15,16]. Future studies should prove whether these measures indeed improved the feasibility.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Even though the proportion of women was much higher than that of men, the number of men was high enough for comparison. Moreover, the previous studies have shown contradictory sex related results on the time to RTW among TKA patients (20,35).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, patients who had a slower return to work often reported that comorbidities, especially musculoskeletal like low back pain or OA affecting other joints, prevented their RTW even when the surgical outcome was positive [40]. However, the most recent review on prognostic factors for return to work concluded that based on 14 studies and 3073 patients, the most important prognostic factors associated with a slower or no RTW were a more physically demanding job and preoperative absence from work [41].…”
Section: Prognostic Factors For Not Returning To Workmentioning
confidence: 99%